The pore forming capacity of Sticholysin I in dipalmitoyl phosphatidyl vesicles is tuned by osmotic stress. (March 2017) - Ahumada, M.; Calderon, C.; Lissi, E.; Alvarez, C.; Lanio, M.E.; Pazos, F.
Highlights: Hypotonic gradients improve the pore forming capacity of rSt I molecules, even in pure DPPC large unilamellar liposomes. In hypotonic conditions, the pore-formation process mediated by rSt I becomes less dependent on the presence of sphingomyelin. In DPPC liposomes, non-active toxins become active by a hypotonic imbalance in a similar way to those liposomes containing SM as a second component. Abstract: The osmotic condition modulates the properties of liposomes, particularly those related to their stability and response to external agents such as membrane-active proteins or peptides. In a previous work, we have demonstrated that an osmotic shock can increase, per se, water influx/efflux and the exit of the fluorophore calcein entrapped in the aqueous pool of dipalmitoylphosphatidylcholine (DPPC) and DPPC:sphingomyelin (SM) large unilamellar vesicles (LUVs), suggesting a loss of integrity of the liposome bilayer. In the present work, we have extended our study in order to assess how an osmotic imbalance prior to or synchronous with the addition of a recombinant variant of the pore-forming toxin sticholysin I (rSt I) modifies its pore forming capacity in DPPC and DPPC:SM (1:1) LUVs. Our results conclusively show the capacity of hypotonic gradients to improve the pore forming capacity of rSt I molecules, even in pure DPPC liposomes, rendering pore-formation less dependent on the presence of sphyngomyelin. In fact, non-active toxins in DPPC liposomes become active by a hypotonic imbalance in a similar way to those containing SM as a second component.